2015
DOI: 10.1158/1078-0432.ccr-15-0866
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Lipid Nanoparticle Potently Silences Clusterin and Delays Progression When Combined with Androgen Receptor Cotargeting in Enzalutamide-Resistant Prostate Cancer

Abstract: Purpose: Lipid nanoparticle (LNP) formulations facilitate tumor uptake and intracellular processing through an enhanced permeation and retention effect (EPR), and currently multiple products are undergoing clinical evaluation. Clusterin (CLU) is a cytoprotective chaperone induced by androgen receptor (AR) pathway inhibition to facilitate adaptive survival pathway signaling and treatment resistance. In our study, we investigated the efficacy of siRNA tumor delivery using LNP systems in an enzalutamide-resistant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 40 publications
0
51
0
1
Order By: Relevance
“…It is argued that management of cancer is more feasible and holds better promise with the use of drug combinations that can hit multiple targets (8–11). Combination chemotherapy has several advantages such as lower dose requirement which subsequently lessens the side effects and circumvents drug resistance; and inhibits or delays metastasis (1218). Zhang et al (13) showed that genistein enhances the response to cabazitaxel treatment in mCRPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that management of cancer is more feasible and holds better promise with the use of drug combinations that can hit multiple targets (8–11). Combination chemotherapy has several advantages such as lower dose requirement which subsequently lessens the side effects and circumvents drug resistance; and inhibits or delays metastasis (1218). Zhang et al (13) showed that genistein enhances the response to cabazitaxel treatment in mCRPC cells.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of such innate immune responses is known as a bottleneck in the clinical development of RNAi drugs. Meanwhile, to avoid such an intrinsic issue, the siRNA of Patisiran (ONPATTRO ® ), the first approved therapeutic form of RNAi that was originally formulated in lipid nanoparticles, is directly conjugated with an N ‐acetylgalactosamine in this formulation, which can facilitate the delivery of RNAi molecules to hepatocytes . DFP‐10825, an RNAi formulation for local administration, avoids such systemic adverse events, because very little of the TS shRNA in the DFP‐10825 formulation escapes into blood circulation from the peritoneal cavity after intraperitoneal injection (Figure A), and as a result, the formulation does not accumulate in immune organs such as the spleen (Figure B).…”
Section: Discussionmentioning
confidence: 99%
“…But surprisingly, clusterin targeting oligonucleotides did not show favorable benefit in a recent clinical trial . However, co‐targeting clusterin and AR delayed the tumor growth of Enz‐resistant PCa in preclinical studies …”
Section: Molecular Chaperones Stabilize the Armentioning
confidence: 99%